Two new species of Plectromerus Haldeman (Coleoptera: Cerambycidae) from the West Indies - Micheli, Charyn J.; Nearns, Eugenio H. (Zootaxa, 2005)
Two new species of Curiini (Coleoptera: Cerambycidae: Cerambycinae), Plectromerus lingafelteri from the Dominican Republic and Plectromerus ramosi from Puerto Rico and the Virgin Islands are described. Features distinguishing the new species from their congeners are presented. Plectromerus distinctus (Cameron), previously synonymized with P. serratus (Cameron), is restored as a valid species.Dos nuevas especies de Curiini (Coleoptera: Cerambycidae: Cerambycinae), Plectromerus lingafelteri de la República Dominicana y Plectromerus ramosi de Puerto Rico y las Islas Vírgenes se describen. Se incluyen características para diferenciar estas especies de otros miembros del género. Plectromerus distinctus (Cameron), previamente sinonimizada con P. serratus (Cameron), se reconoce como especie válida.